A high-performance waterproof material, its preparation method and application
By adding hydrophobically modified MoS2@ chopped basalt fibers and zirconium-modified alumina nanosheets to the waterproof material, combined with silane coupling agent and other components, the problem of insufficient adhesion and wear resistance of existing waterproof materials is solved. Achieve the improvement of high-performance waterproof materials.
Patent Information
- Application Number
- CN202311854545.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-12-29
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2043-12-29
AI Technical Summary
The existing waterproof materials have shortcomings in adhesion and wear resistance, and it is difficult to meet the requirements of building waterproofing projects for high-performance waterproofing materials.
By adding hydrophobically modified MoS2@ chopped basalt fibers and zirconium-modified alumina nanosheets, combined with silane coupling agent, wetting agent and cosolvent, the waterproofing, adhesion and wear resistance of the waterproof material are promoted, etc. Improvement.
It significantly improves the waterproof performance, adhesion and wear resistance of waterproof materials, and meets the demand for high-performance waterproof materials in building waterproof projects.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of waterproof materials, and more specifically, relates to a high-performance waterproof material and a preparation method and application thereof. Background Art
[0002] With the rapid development of the construction industry, the requirements for building waterproofing projects are getting higher and higher. New building waterproofing materials are constantly emerging. Multifunctional waterproofing materials with excellent performance, good weather resistance and environmental protection have shown strong vitality. Waterproof coatings occupy an important position in waterproof materials. Due to the convenience of construction, their application range is getting wider and wider, especially polymer series waterproof coatings, which have a trend of catching up. Silicone acrylic emulsion waterproof coatings are the rising star among polymer waterproof coatings.
[0003] Silicone-acrylic emulsion is a composite emulsion formed by the copolymerization of nano-silica and acrylate through titanium chelation cross-linking. It has the flexibility and high elasticity of organic materials and the rigidity and durability of inorganic materials - nano-silica-acrylate composite emulsion.
[0004] CN117089253A discloses a stain-resistant environmentally friendly artistic paint and a preparation method thereof. A stain-resistant environmentally friendly artistic paint comprises the following raw materials in parts by weight: 60-85 parts of silicone-acrylic emulsion, 6-10 parts of hydroxyethyl cellulose, 5-8 parts of ethylene glycol, 6-10 parts of thickener, 40-65 parts of natural white sand, 0.2-0.5 parts of defoamer, 5-7 parts of film-forming aid, 2-5 parts of waterproofing agent, 2-6 parts of antifouling agent, and 10-15 parts of water; the antifouling agent is prepared from raw materials including polyarylethersulfone, N-(5-methylacrylamide-2,3,4-hydroxybenzyl)acrylamide, N-methylacrylamide, organic solvent, and 3-mercaptopropyltrimethoxysilane through steps including mixing, stirring, and heating. The present application has the advantages of improving the stain resistance and initial crack resistance of the coating.
[0005] CN115895372A discloses a waterproof and heat-insulating exterior wall coating and its preparation method. A waterproof and heat-insulating exterior wall coating comprises the following raw materials in parts by weight: 50-60 parts of silicone-acrylic emulsion; 5-6 parts of fluorocarbon resin; 5-7 parts of filler; 3-5 parts of thickener; 1-3 parts of leveling agent; 1-3 parts of defoamer; 2-4 parts of film-forming mixed auxiliary agent; 3-6 parts of reflective heat-insulating powder mixture; 25-35 parts of water; the film-forming mixed auxiliary agent comprises the following raw materials: dodecyl alcohol ester, dipropylene glycol butyl ether, and dipropylene glycol methyl ether; and the weight ratio of dodecyl alcohol ester, dipropylene glycol butyl ether, and dipropylene glycol methyl ether is (1-1.5):1:(1.8-2.4); the reflective heat-insulating powder mixture comprises the following raw materials: titanium dioxide, silicon dioxide, and aluminum oxide, and the weight ratio of titanium dioxide, silicon dioxide, and aluminum oxide is (0.5-0.8):(1.3-1.6):1. The waterproof and heat-insulating exterior wall coating of the present application can take into account excellent waterproof and heat-insulating properties during application.
[0006] Although the materials in the above documents have certain waterproof properties, their adhesion, wear resistance, etc. are obviously insufficient. Summary of the invention
[0007] The technical problem to be solved by the present invention is to overcome the defects and shortcomings of the prior art and provide a high-performance waterproof material and its preparation method and application. The material includes the following raw materials in parts by weight: 25-35 parts of silicone acrylic emulsion, 25-35 parts of silicone oil, 60-80 parts of organic solvent, 15-25 parts of silane coupling agent, 6-12 parts of hydrophobically modified MoS2@chopped basalt fiber, 3-7 parts of zirconium-modified alumina nanosheets, 2-4 parts of wetting agent; 1-3 parts of cosolvent. By adding hydrophobically modified MoS2@chopped basalt fiber and zirconium-modified alumina nanosheets, and in combination with silane coupling agent, wetting agent and cosolvent, the interaction between the components jointly promotes the improvement of waterproofing, adhesion, wear resistance, etc. of the waterproof material.
[0008] The purpose of the present invention is to provide a high-performance waterproof material.
[0009] Another object of the present invention is to provide a method for preparing a high-performance waterproof material.
[0010] Another object of the present invention is to provide a use of a high-performance waterproof material.
[0011] The above-mentioned purpose of the present invention is achieved through the following technical solutions:
[0012] A high-performance waterproof material comprises the following raw materials in parts by weight: 25-35 parts of silicone-acrylic emulsion, 25-35 parts of silicone oil, 60-80 parts of organic solvent, 15-25 parts of silane coupling agent, 6-12 parts of hydrophobically modified MoS2@chopped basalt fiber, 3-7 parts of zirconium-modified alumina nanosheets, 2-4 parts of wetting agent and 1-3 parts of cosolvent.
[0013] In a preferred embodiment, the length of the chopped basalt fiber is 0.5-3.5 μm, and the aspect ratio is 10-40:1; the silane coupling agent is at least one of KH-550, KH-560, and KH-570; and the organic solvent is ethanol or propanol.
[0014] In a preferred embodiment, the silicone-acrylic emulsion has a silicon content of not less than 6% and a solid content of 35-45%.
[0015] In the present invention, a further preferred technical solution is that the hydrophobically modified MoS2@chopped basalt fiber;
[0016] (1) placing short basalt fiber, molybdenum source and thiourea in deionized water and stirring to obtain a mixed solution; then transferring the mixture to a high pressure reactor for hydrothermal reaction at 160-200° C. for 16-24 h, washing and vacuum drying at 60-90° C. for 10-20 h to obtain MoS2@short basalt fiber;
[0017] (2) The MoS2@chopped basalt fibers and hexadecyltrimethoxysilane obtained in step (1) are ultrasonically dispersed in ethanol water, and then stirred and reacted at 40-80° C. for 2-6 h to obtain hydrophobically modified MoS2@chopped basalt fibers.
[0018] Preferably, in step (1), the molybdenum source includes at least one of sodium molybdate, potassium molybdate or ammonium molybdate; and the ratio of the chopped basalt fiber, the molybdenum source and thiourea is: 100 g: 4-8 mmol: 10-20 mmol.
[0019] Preferably, in step (2), the volume ratio of ethanol to water is 4:1; the mass ratio of MoS2@chopped basalt fiber to hexadecyltrimethoxysilane is 1:0.3-0.5.
[0020] In the present invention, a further preferred technical solution is a method for preparing the zirconium-modified alumina nanosheets;
[0021] Graphene oxide, zirconium chloride, aluminum chloride and urea are ultrasonically dispersed in deionized water, then stirred in a water bath at 80-90°C for 2-4 hours, centrifuged, filtered, dried at 60°C to constant weight, and then calcined at 800-900°C for 2-4 hours to obtain zirconium-modified aluminum oxide nanosheets.
[0022] Preferably, the ratio of graphene oxide, zirconium chloride, aluminum chloride and urea is 1 g: 2-4 mmol: 1-2 mol: 1.5-2.5 mol.
[0023] Another technical solution of the present invention is a method for preparing a high-performance waterproof material, which comprises the following steps: the silicone-acrylic emulsion and the organic solvent are first stirred and mixed evenly, then the hydrophobically modified MoS2@chopped basalt fibers and zirconium-modified alumina nanosheets, silane coupling agent and silicone oil are fully stirred and added thereto, and finally a wetting agent and a co-solvent are added to obtain a hydrophobic coating.
[0024] Another technical solution of the present invention is the use of the high-performance waterproof material, wherein the waterproof material is used in the waterproof field.
[0025] The present invention has the following beneficial effects:
[0026] The present invention adds hydrophobically modified MoS2@chopped basalt fibers and zirconium-modified alumina nanosheets, and cooperates with a silane coupling agent, a wetting agent and a cosolvent to jointly promote the improvement of the waterproofing, adhesion, wear resistance and the like of the waterproof material through the interaction between the components. DETAILED DESCRIPTION
[0027] The present invention is further described below with reference to specific examples, but the examples do not limit the present invention in any form. Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.
[0028] The silicone-acrylic emulsion used in the examples and comparative examples has a silicon content of 10 wt % and a solid content of 40 %; the wetting agent is OP-10; and the cosolvent is propylene glycol.
[0029] Unless otherwise specified, the reagents and materials used in the following examples are commercially available.
[0030] Example 1
[0031] A high-performance waterproof material comprises the following raw materials in parts by weight: 35 parts of silicone-acrylic emulsion, 25 parts of silicone oil, 80 parts of organic solvent, 15 parts of silane coupling agent, 12 parts of hydrophobically modified MoS2@chopped basalt fiber, 3 parts of zirconium-modified alumina nanosheets, 4 parts of wetting agent; 1 part of cosolvent; the silane coupling agent is KH-550; and the organic solvent is ethanol.
[0032] The length of the chopped basalt fiber is 3.5 μm, and the aspect ratio is: 40:1;
[0033] The preparation method of hydrophobically modified MoS2@chopped basalt fiber is as follows;
[0034] (1) 100 g of chopped basalt fiber, 8 mmol of sodium molybdate and 20 mmol of thiourea were placed in 200 mL of deionized water and stirred to obtain a mixed solution; then the mixture was transferred to a high-pressure reactor for hydrothermal reaction at 200 °C for 16 h, washed and vacuum dried at 90 °C for 10 h to obtain MoS2@chopped basalt fiber;
[0035] (2) 10 g of the MoS2@chopped basalt fiber obtained in step (1) and 5 g of hexadecyltrimethoxysilane were ultrasonically dispersed in 150 mL of ethanol and water, with the volume ratio of ethanol to water being 4:1; and then stirred and reacted at 80°C for 2 h to obtain hydrophobically modified MoS2@chopped basalt fiber.
[0036] The preparation method of zirconium-modified alumina nanosheets is as follows;
[0037] 1 g of graphene oxide, 4 mmol of zirconium chloride, 1 mol of aluminum chloride and 1.5 mol of urea were ultrasonically dispersed in 100 mL of deionized water, then stirred in a water bath at 90 ° C for 2 h, centrifuged, filtered, dried at 60 ° C to constant weight, and then calcined at 900 ° C for 2 h to obtain zirconium-modified aluminum oxide nanosheets.
[0038] A preparation method of a high-performance waterproof material comprises the following steps: firstly stirring and mixing a silicone-acrylic emulsion and an organic solvent evenly, then stirring hydrophobically modified MoS2@chopped basalt fibers and zirconium-modified alumina nanosheets, a silane coupling agent and silicone oil sufficiently, then adding them thereto, and finally adding a wetting agent and a co-solvent to obtain a hydrophobic coating.
[0039] Example 2
[0040] A high-performance waterproof material comprises the following raw materials in parts by weight: 30 parts of silicone-acrylic emulsion, 30 parts of silicone oil, 70 parts of organic solvent, 20 parts of silane coupling agent, 10 parts of hydrophobically modified MoS2@chopped basalt fiber, 5 parts of zirconium-modified alumina nanosheets, 3 parts of wetting agent; 2 parts of cosolvent; the silane coupling agent is KH-570; and the organic solvent is ethanol.
[0041] The length of the chopped basalt fiber is 2 μm, and the aspect ratio is 20:1;
[0042] The preparation method of hydrophobically modified MoS2@chopped basalt fiber is as follows;
[0043] (1) 100 g of chopped basalt fiber, 6 mmol of potassium molybdate and 16 mmol of thiourea were placed in 200 mL of deionized water and stirred to obtain a mixed solution; then the mixture was transferred to a high-pressure reactor for hydrothermal reaction at 180 ° C for 20 h, washed and vacuum dried at 80 ° C for 16 h to obtain MoS2@chopped basalt fiber;
[0044] (2) 10 g of the MoS2@chopped basalt fiber obtained in step (1) and 4 g of hexadecyltrimethoxysilane were ultrasonically dispersed in 150 mL of ethanol and water, with the volume ratio of ethanol to water being 4:1; and then stirred and reacted at 60°C for 4 h to obtain hydrophobically modified MoS2@chopped basalt fiber.
[0045] The preparation method of zirconium-modified alumina nanosheets is as follows;
[0046] 1 g of graphene oxide, 3 mmol of zirconium chloride, 1.5 mol of aluminum chloride and 2 mol of urea were ultrasonically dispersed in 100 mL of deionized water, then stirred in a water bath at 85 °C for 3 h, centrifuged, filtered, dried at 60 °C to constant weight, and then calcined at 850 °C for 3 h to obtain zirconium-modified alumina nanosheets.
[0047] A preparation method of a high-performance waterproof material comprises the following steps: firstly stirring and mixing a silicone-acrylic emulsion and an organic solvent evenly, then stirring hydrophobically modified MoS2@chopped basalt fibers and zirconium-modified alumina nanosheets, a silane coupling agent and silicone oil sufficiently, then adding them thereto, and finally adding a wetting agent and a co-solvent to obtain a hydrophobic coating.
[0048] Example 3
[0049] A high-performance waterproof material comprises the following raw materials in parts by weight: 25 parts of silicone-acrylic emulsion, 35 parts of silicone oil, 60 parts of organic solvent, 25 parts of silane coupling agent, 6 parts of hydrophobically modified MoS2@chopped basalt fiber, 7 parts of zirconium-modified alumina nanosheets, 2 parts of wetting agent; 3 parts of cosolvent; the silane coupling agent is KH-560; and the organic solvent is propanol.
[0050] The length of the chopped basalt fiber is 0.5 μm, and the aspect ratio is 10:1;
[0051] The preparation method of hydrophobically modified MoS2@chopped basalt fiber is as follows;
[0052] (1): 100 g of chopped basalt fiber, 4 mmol of ammonium molybdate and 10 mmol of thiourea were placed in 200 mL of deionized water and stirred to obtain a mixed solution; then the mixture was transferred to a high-pressure reactor for hydrothermal reaction at 160 ° C for 24 h, washed and vacuum dried at 60 ° C for 20 h to obtain MoS2@chopped basalt fiber;
[0053] (2) 10 g of the MoS2@chopped basalt fiber obtained in step (1) and 3 g of hexadecyltrimethoxysilane were ultrasonically dispersed in 150 mL of ethanol and water, with the volume ratio of ethanol to water being 4:1; and then stirred and reacted at 40°C for 6 h to obtain hydrophobically modified MoS2@chopped basalt fiber.
[0054] The preparation method of zirconium-modified alumina nanosheets is as follows;
[0055] 1 g of graphene oxide, 2 mmol of zirconium chloride, 2 mol of aluminum chloride and 2.5 mol of urea were ultrasonically dispersed in 100 mL of deionized water, then stirred in a water bath at 80 ° C for 4 h, centrifuged, filtered, dried at 60 ° C to constant weight, and then calcined at 800 ° C for 4 h to obtain zirconium-modified aluminum oxide nanosheets.
[0056] A preparation method of a high-performance waterproof material comprises the following steps: firstly stirring and mixing a silicone-acrylic emulsion and an organic solvent evenly, then stirring hydrophobically modified MoS2@chopped basalt fibers and zirconium-modified alumina nanosheets, a silane coupling agent and silicone oil sufficiently, then adding them thereto, and finally adding a wetting agent and a co-solvent to obtain a hydrophobic coating.
[0057] Comparative Example 1
[0058] An equal amount of hydrophobically modified chopped basalt fibers was used to replace the hydrophobically modified MoS2@chopped basalt fibers, and the other steps and conditions were exactly the same as those in Example 2.
[0059] The preparation method of the hydrophobically modified chopped basalt fiber is as follows:
[0060] 10 g of chopped basalt fiber and 4 g of hexadecyltrimethoxysilane were ultrasonically dispersed in 150 mL of ethanol water, with the volume ratio of ethanol to water being 4:1; then the reaction was stirred at 60°C for 4 h to obtain hydrophobically modified MoS2@chopped basalt fiber.
[0061] Comparative Example 2
[0062] MoS2@chopped basalt fiber was not subjected to hydrophobic modification, and other steps and conditions were exactly the same as those in Example 2.
[0063] Comparative Example 3
[0064] An equal amount of aluminum oxide nanosheets was used to replace the zirconium-modified aluminum oxide nanosheets, and the other steps and conditions were exactly the same as those in Example 2.
[0065] The preparation method of aluminum oxide nanosheets is as follows;
[0066] 1 g of graphene oxide, 1.503 mol of aluminum chloride and 2 mol of urea were ultrasonically dispersed in 100 mL of deionized water, then stirred in a water bath at 85°C for 3 h, centrifuged, filtered, dried at 60°C to constant weight, and then calcined at 850°C for 3 h to obtain aluminum oxide nanosheets.
[0067] Comparative Example 4
[0068] An equal amount of zirconium-modified alumina was used to replace the zirconium-modified alumina nanosheets, and the other steps and conditions were exactly the same as those in Example 2.
[0069] The preparation method of zirconium-modified alumina nanosheets is as follows;
[0070] 3 mmol of zirconium chloride, 1.5 mol of aluminum chloride and 2 mol of urea were ultrasonically dispersed in 100 mL of deionized water, then stirred in a water bath at 85°C for 3 h, centrifuged, filtered, dried at 60°C to constant weight, and then calcined at 850°C for 3 h to obtain zirconium-modified alumina.
[0071] Comparative Example 5
[0072] 15 parts of hydrophobically modified MoS2@chopped basalt fibers were used to replace 10 parts of hydrophobically modified MoS2@chopped basalt fibers and 5 parts of zirconium-modified alumina nanosheets, and the other steps and conditions were exactly the same as those in Example 2.
[0073] Place the product under normal conditions and water mist conditions for 15 hours to test its waterproof performance.
[0074] Among them, the peel strength standard: GBT 7122-1996
[0075] Wear resistance test standard: GB / T1768-1979
[0076]
[0077] It can be seen from Examples 1-3 and Comparative Examples 1-5 that the high-performance waterproof material prepared by the present invention has excellent peel strength and wear resistance, while the performance deteriorates when hydrophobic modification is omitted, zirconium modification is not performed, and the sheet is converted into powder.
[0078] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.
Claims
1. A high-performance waterproof material, characterized in that: The invention comprises the following raw materials in parts by weight: 25-35 parts of silicone acrylic emulsion, 25-35 parts of silicone oil, 60-80 parts of organic solvent, 15-25 parts of silane coupling agent, 6-12 parts of hydrophobically modified MoS2@chopped basalt fiber, 3-7 parts of zirconium-modified alumina nanosheets, 2-4 parts of wetting agent and 1-3 parts of cosolvent; The hydrophobically modified MoS2@chopped basalt fiber: (1) placing short basalt fiber, molybdenum source and thiourea in deionized water and stirring to obtain a mixed solution; then transferring to a high-pressure reactor for hydrothermal reaction, wherein the hydrothermal reaction conditions are: reacting at 160-200° C. for 16-24 h, washing, and vacuum drying at 60-90° C. for 10-20 h to obtain MoS2@short basalt fiber; the ratio of the short basalt fiber, molybdenum source and thiourea is: 100 g: 4-8 mmol: 10-20 mmol; (2) ultrasonically dispersing the MoS2@chopped basalt fiber and hexadecyltrimethoxysilane obtained in step (1) into ethanol water, and then stirring and reacting at 40-80° C. for 2-6 hours to obtain hydrophobically modified MoS2@chopped basalt fiber; the mass ratio of the MoS2@chopped basalt fiber to the hexadecyltrimethoxysilane is 1:0.3-0.5; The preparation method of the zirconium-modified alumina nanosheets: Graphene oxide, zirconium chloride, aluminum chloride and urea are ultrasonically dispersed in deionized water, and then stirred in a water bath at 80-90° C. for 2-4 hours, centrifuged, filtered, dried at 60° C. to constant weight, and then calcined at 800-900° C. for 2-4 hours to obtain zirconium-modified aluminum oxide nanosheets; the ratio of graphene oxide, zirconium chloride, aluminum chloride and urea is 1 g: 2-4 mmol: 1-2 mol: 1.5-2.5 mol; In step (1), the molybdenum source includes at least one of sodium molybdate, potassium molybdate or ammonium molybdate.
2. A high performance waterproof material according to claim 1, characterized in that: The length of the chopped basalt fiber is 0.5 to 3.5 μm, and the aspect ratio is 10 to 40:1; the silane coupling agent is at least one of KH-550, KH-560, and KH-570; and the organic solvent is ethanol or propanol.
3. A high performance waterproof material according to claim 1, characterized in that: The silicon content of the silicone-acrylic emulsion is not less than 6%, and the solid content is 35-45%.
4. A high performance waterproof material according to claim 1, characterized in that: In step (2), the volume ratio of ethanol to water is 4:
1.
5. A method for preparing a high-performance waterproof material according to any one of claims 1 to 4, characterized in that: The preparation method comprises the following steps: firstly stirring and mixing the silicone-acrylic emulsion and the organic solvent evenly, then stirring the hydrophobically modified MoS2@chopped basalt fibers and zirconium-modified alumina nanosheets, silane coupling agent and silicone oil sufficiently, then adding them, and finally adding a wetting agent and a cosolvent to obtain a hydrophobic coating.
6. Use of a high-performance waterproof material according to any one of claims 1 to 4, characterized in that: The waterproof material is used in the waterproof field.
Citation Information
Patent Citations
Stain-resistant environment-friendly art coating and preparation method thereof
CN117089253A
Preparation method and application of nano ZrO2 / Al2O3 composite material
CN113683916A
Hydrophobic coating for natural gas gasifier and preparation method of hydrophobic coating
CN117229687A